Innovation Policy Developmet Conceptual Framework for National Resource Security Providing - PROKOPENKO, Olha; OMELYANENKO, Vitaliy; KLISINSKI, Janusz (Journal of Environmental Management and Tourism, 2019)
The article deals with the problem of resource security and its providing through the innovation and technological systems development. Also authors have considered international aspect of resource security and its technological providing based on resource & innovation linkages and global value chains (GVCs) factor. In study authors have proposed to consider «resource nationalism» concept as a system of government's efforts, based on national and international factors, to gain greater benefits from available natural resources using innovation development strategy without any detriment to private companies. Resource management were considered within the necessity to follow long-term strategy of resource use, including the context of goals set achieving for several decades or even centuries to come. On example of United States authors have considered resource security policy, which combines international trade and innovation instruments. Authors have considered the basics of systemic strategy of resource security ensuring in globalization context within the national economic security. By analogy with main definitions of any national economic security components authors have distinguished three basic economic components of resource security management system (purposeful economic process, economic actors, environment). The authors have developed the innovation and technological resource security support, based on resource management and technology request processes. Based on dematerialization management aspects and risk types innovation and technological development priorities within the national resource security were proposed.